Discourse Markers in English & Arabic: A contrastive Study - Abdulkhaliq Majeed, Ibtisam; Salih Hmoody, Eman (Opción, 2019)
Many words which might be claimed to be DMs arise commonly in speech, but no principled grounds exist on which to disclaim DM repute to comparable objects which might be in large part located in written discourse The role of the discourse markers which are words or phrases in the linguistic system to make relations between topics in the discourse .They are important but use them when necessary in the informal speech as if we say them a lot make the speech artificial. The grammatical structure has a subject, verb, or object.